Anxiety, depressed mood, self-esteem, and traumatic stress symptoms among distant witnesses of the 9/11 terrorist attacks: transitory responses and psychological resilience - Matt, Georg E.; Vázquez, Carmelo (The Spanish Journal of Psychology, 2008)
Posttraumatic stress related to the September 11, 2001 terrorist attacks and general psychological distress were examined in six cohorts of college students (N=5,412) enrolled at an American public university between Spring 2000 and Fall 2002 some 2,500 miles from New York. Consistent with data from Schuster et al.’s (2001) national survey, which used a very low threshold criterion, our findings revealed that 44% of women and 32% of men experienced at least one symptom of posttraumatic stress 6-17 days after the attacks. In contrast to these results, depression levels showed only small differences, and self-esteem and trait anxiety showed no changes. Findings indicate that 9/11-related stress responses among distant witnesses were very mild, transitory and focused in scope, suggesting resilience with respect to broader psychological and psychopathological reactions. Findings are discussed with respect to the role of physical and psychological proximity on the reactions to traumatic events in the general population.